2021
DOI: 10.1155/2021/5593223
|View full text |Cite
|
Sign up to set email alerts
|

National Health-Oriented Hazard Assessment in Iran Based on the First Priority for Action in Sendai Framework for Disaster Risk Reduction 2015–2030

Abstract: Background. Understanding disaster risk is the first priority for action based on the Sendai Framework for Disaster Risk Reduction 2015–2030 (SFDRR), and hazard assessment is the first step in the assessment of disaster risks. Therefore, assessing health-oriented hazards is the first measure in disaster risk assessment in the medical universities area in Iran. This article introduces a national experience and results obtained from designing a national tool for defining and assessment of health-oriented hazards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In addition to the hazards identified in this study, EMS facilities were also exposed to other hazards that were less serious compared to the five main hazards detailed above. Similarly, Khankeh et al (2021) [ 20 ] introduced a hazard assessment tool and identified the first top 20 hazards rated by Iranian universities of medical sciences. They reported road traffic accidents, earthquakes, droughts, floods, and epidemics to be the five most serious health hazards.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the hazards identified in this study, EMS facilities were also exposed to other hazards that were less serious compared to the five main hazards detailed above. Similarly, Khankeh et al (2021) [ 20 ] introduced a hazard assessment tool and identified the first top 20 hazards rated by Iranian universities of medical sciences. They reported road traffic accidents, earthquakes, droughts, floods, and epidemics to be the five most serious health hazards.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the hazards identi ed in this study, EMS facilities were also exposed to other hazards that were less serious compared to the ve main hazards detailed above. Similarly, Khankeh et al (2021) (11) introduced a hazard assessment tool and identi ed the rst top 20 hazards rated by Iranian universities of medical sciences. They reported tra c accidents, earthquakes, droughts, oods, and epidemics to be the ve most serious health hazards.…”
Section: Discussionmentioning
confidence: 99%
“…Iran ranks fourth among the countries at risk for natural disasters. Of the 40 types of natural disasters observed in the world, 31 occur in Iran with an emphasis on earthquake in comparison to other hazards [ 1 ]. Also, with the increase in the number of motor vehicles, the number of fatalities due to accidents has increased and has become a threat to health systems in developing and developed countries [ 2 ].…”
Section: Introductionmentioning
confidence: 99%